WORKLOAD ANALYSIS TO DETERMINE THE NUMBER OF LABOR IN SOAP PRODUCTION USING THE FULL TIME EQUIVALENT METHOD: A CASE STUDY OF PT. XY - Aisyah Fitri Wahyulistiani; M Tutuk Safirin; Tranggono Tranggono; Dirgahayu Lantara (Journal of Industrial Engineering Management, 2022)
PT. XY is a manufacturing company in Surabaya that produces household hygienic goods, such as soap bars and liquid soap. It is known that the actual condition of production in the company is still not optimal due to the uneven workload at each work station. This also results in workers experiencing excessive workloads that cause fatigue or illness, and there are more unemployed, causing decreased performance. According to the problems above, this research was conducted to determine the value of the workload received and to find out the optimal number of workers so that in the future work can be more effective and efficient. Solving workload analysis problems in this study using the Full Time Equivalent method. Based on the results of the study, it was known that the workload of the bar soap production section was 16 people, 3 people were found in the Normal category and 13 people experienced the workload in the Overload category. While the results of the workload of the liquid soap production section were 19 people, 6 people were found in the Normal category and 13 people experienced a workload in the Underload category. For calculating the optimal number of workers, the results obtained for the production of bar soap need to add 7 people to the workforce and liquid soap production to reduce the workforce by 3 people.